تأثير نموذج التعلم القائم على حل المشكلات على تحسين مهارات الكتابة - Magviroh, Dina Aulia; Hidayah, Rohmatun Nurul; Mustain, Mustain (Yayasan Mutiara Hati Moeslem, 2025)
Writing skills are an important aspect of Arabic language learning, but they remain a challenge for students, particularly at As-Sa'diyah Boarding School. Students in class 1E have difficulty constructing appropriate sentences, choosing the right vocabulary, and expressing their ideas coherently. One of the causes of this is that learning does not actively involve students. This study uses a quantitative approach with a quasi-experimental design. Data was collected through observation, interviews, documentation, tests, and questionnaires, and then analyzed using a t-test. The results of this study show that the implementation of the Problem-Based Learning model was carried out through five core stages: problem orientation, task organization, group investigation, presentation of results, and final reflection. This approach encouraged students to be more active, collaborative, and skilled in constructing Arabic texts in a coherent and contextual manner. The results of the one-tailed paired t-test (df = 16) showed that t-calculated = 9.443 was greater than t-table = 1.746 at α = 0.05, with p < 0.001. Therefore, H0 was rejected and Ha was accepted. Meanwhile, the control group only experienced a small increase from 68.82 to 70.23, which was not statistically significant. The improvements in the experimental group included more coherent sentence structure, more appropriate vocabulary use, and the ability to express ideas more clearly and logically. The questionnaire results showed that 88.24% of students felt that the PBL model made it easier for them to understand and write Arabic texts in an engaging, active, and contextual manner.